Psychological Peculiarities of Senior Pupils with Machiavellian Tendencies - Fedotova, Tetyana V. (Psychological Prospects Journal, 2017)
In the article it is theoretically observed the phenomenon of Machiavellism in the works of R. Christie and F. Geis (defining of “the general model of behavioral display” of a person with high level of Machiavellism which in the future became a grounding for depth research of this phenomenon), D. Braginsky (clarification of peculiarities of Machiavellism manifestation among children aged 10), S. Rey and M. Gapta (studying conscious and unconscious inheritance of Machiavellian believes of parents by children), J. Thibaud, C. Hickey and P. Gumpert (studying of ethical attitudes of people depending on the level of Machiavellism), N. Barber (studying of Machiavellism in family relations), A. Ruslina (studying psychological peculiarities of Machiavellian personalities), V. Znakova (connection of Machiavellism with moral qualities of a personality).The results of empirical research let us state the following: among girls it was found out that 55% of them have a high level of Machiavellism and among boys this index was only 38% of the respondents. In general we may say that high level of Machiavellism among girls is socially cultured as it is encouraged by significant adults and is observed to some extent as a norm of behavior. Girls with high level of Machiavellism are characterized by introversion, neuroticism and irritability which underlines their excessive anxiety, fear, frequent changes of mood and feeling of loneliness. In communication they often resort to verbal and indirect aggression which may be expressed in everyday gossips, evil jokes, threats and negative attitude towards their environment. Boys with high level of Machiavellism are predisposed to antisocial behavior, aggressive displays and inadequate emotional reactions. In communication with peers they differ in their proneness to conflict, unsociability, selfishness and indifference, they mainly resort to verbal aggression thereby carrying out significant social pressure on an interlocutor.Key words: machiavellism, manipulation, introversion, extroversion, neuroticism, psychoticism, aggression.